Asciminib vs bosutinib in chronic-phase chronic myeloid leukemia previously treated with at least two tyrosine kinase inhibitors: longer-term follow-up of ASCEMBL - Hochhaus, Andreas; Réa, Delphine; Boquimpani, Carla; Minami, Yosuke; Cortés, Jorge Eduardo; Hughes, Timothy P.; Apperley, Jane F.; Lomaia, Elza; Voloshin, Sergey; Turkina, Anna; Kim, Dong-Wook; Abdo, Andre; et al. (Leukemia, 2023)
Asciminib, the first BCR::ABL1 inhibitor that Specifically Targets the ABL Myristoyl Pocket (STAMP), is approved worldwide for the treatment of adults with Philadelphia chromosome-positive chronic myeloid leukemia in chronic phase (CML-CP) treated with ≥2 prior tyrosine kinase inhibitors (TKIs). In ASCEMBL, patients with CML-CP treated with ≥2 prior TKIs were randomized (stratified by baseline major cytogenetic response [MCyR]) 2:1 to asciminib 40 mg twice daily or bosutinib 500 mg once daily. Consistent with previously published primary analysis results, after a median follow-up of 2.3 years, asciminib continued to demonstrate superior efficacy and better safety and tolerability than bosutinib. The major molecular response (MMR) rate at week 96 (key secondary endpoint) was 37.6% with asciminib vs 15.8% with bosutinib; the MMR rate difference between the arms, after adjusting for baseline MCyR, was 21.7% (95% CI, 10.53-32.95; two-sided p = 0.001). Fewer grade ≥3 adverse events (AEs) (56.4% vs 68.4%) and AEs leading to treatment discontinuation (7.7% vs 26.3%) occurred with asciminib than with bosutinib. A higher proportion of patients on asciminib than bosutinib remained on treatment and continued to derive benefit over time, supporting asciminib as a standard of care for patients with CML-CP previously treated with ≥2 TKIs.
Online veröffentlicht: 30. Januar 2023
Gesehen am 18.09.2024